Modern technologies of treatment of choledocholithiasis - Dulat Serikbaiuly; Meirbek Aimagambetov (National Scientific Medical Center, 2017)
The article presents data on the modern methods of treatment of cholecystisis complicated by choledocholithiasis. Methods of surgical treatment of common bile duct stones are increasing with the development of new technologies. Despite this, there is no clear consensus on the "gold standard" in treatment this disease. Old and new approaches include open surgical (including the mini-access method), laparoscopic and endoscopic procedures. The use of mini-invasive technology signifcantly reduces the number of postoperative complications, the period of postoperative rehabilitation of patients, and the mortality rate. The availability of technical resources and professional experience of experts may also play a crucial role in choice of treatment strategy.